CHARACTERISTICS OF RADIOLOGICAL DIAGNOSTICS OF COMPLICATIONS AFTER ABDOMINAL SURGERY AND ABDOMINAL DELIVERY - Mustafayev, A.N. (World of Medicine and Biology, 2025)
The purpose of the study was to determine the diagnostic efficiency of ultrasound examinations and computed tomography in detection of complications after surgery for Crohn’s disease and nonspecific ulcerative colitis, as well as abdominal delivery. The study included 21 women who gave birth by cesarean section. The study also included 40 patients who had previously undergone surgery for colitis and Crohn’s disease. All patients underwent comparative analysis of ultrasound and computed tomography data during the observation period. In none of these cases was ultrasound examination a reliable diagnostic tool for detection of complications after cesarean section. Computed tomography demonstrated very high or complete accuracy in all three cases and proved its high efficiency in diagnostics of complications arising after surgical treatment of colitis and Crohn’s disease.